Binuclear C^C* Cyclometalated Platinum(II) NHC Complexes with Bridging Amidinate Ligands. (18th November 2016) - Leopold, Hendrik; Tenne, Mario; Tronnier, Alexander; Metz, Stefan; Münster, Ingo; Wagenblast, Gerhard; Strassner, Thomas
Abstract: Binuclear C^C* cyclometalated NHC platinum(II) compounds with bridging amidinate ligands were synthesized to evaluate their photophysical properties. Their three‐dimensional structures were determined by a combination of 2D NMR experiments, mass spectrometry, DFT calculations, and solid‐state structure analysis. The bridging amidinate ligands enforce short distances between the platinum centers of the two cyclometalated structures, which gives rise to extraordinary photophysical properties.